Needs-Based Drug and Medical Consumables (MDCs) Planning as a Zine-Qua-Non in Hospitals - Muttaqin, Muttaqin; Kartini Wonsu, Andi Selvi; Yuliati, Andi; Samboteng, Lukman; Aliah, Nurul (PINISI Discretion Review, 2025)
Needs-based drug and medical consumables (MDCs) planning is a Zine Qua Non to ensure optimal patient care in hospitals and healthcare centers. Accurate drug and MDC planning affects the quality of medical services, the effectiveness of resource utilization, operational costs, and patient satisfaction. This research article describes the needs-based drug and MDCs planning system in hospitals. A descriptive case study was conducted at La Mappapenning Regional Hospital in Bone Regency. Data were obtained through observation, documentation, and in-depth interviews with the director, pharmacists, medical personnel, and staff. The study found that needs-based planning at La Mappapenning Regional Hospital can reduce waste of drug and MDCs supplies, accelerate response times to medical needs, and increase patient and family satisfaction. Furthermore, it demonstrates the importance of using a management information system in planning drug and MDCs needs efficiently, effectively, and sustainably. This study recommends collaboration between units in handling a series of drug and MDCs management processes, training for medical personnel and administrative staff, and optimizing the use of the hospital management information system (SIMRS) to support needs-based drug and MDCs planning.